2016
DOI: 10.1111/clr.12752
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcomes of osteotome sinus floor elevation without bone grafts: a clinical retrospective study of 4–9 years

Abstract: Osteotome sinus floor elevation without bone grafts is a predictable treatment modality in the long run. But it should be used with caution when the initial bone height of the edentulous site is lower than 5 mm. The final endo-sinus bone height was found to be positively correlated to implant protrusion length measured on radiographs immediately after implant installation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 37 publications
4
29
0
Order By: Relevance
“…For the studies with longest follow-up visit time (10 years), the 10-year cumulative implant survival rate was 100% in Nedir's study (25 implants), and 91.2% in Caban's study (31/34 implants, 3 failed implants occurred within the 1 st year) 35,36 . The lowest implant survival rate was 90.6% (87 out of 96 implants survived) over 108 months, as is reported by Si et al 38 . For the platelet-grafted TSFE, 4 out of 5 studies reported their 1-year implant survival rates, which ranged between 97.1% and 100% 7,[18][19][20] .…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…For the studies with longest follow-up visit time (10 years), the 10-year cumulative implant survival rate was 100% in Nedir's study (25 implants), and 91.2% in Caban's study (31/34 implants, 3 failed implants occurred within the 1 st year) 35,36 . The lowest implant survival rate was 90.6% (87 out of 96 implants survived) over 108 months, as is reported by Si et al 38 . For the platelet-grafted TSFE, 4 out of 5 studies reported their 1-year implant survival rates, which ranged between 97.1% and 100% 7,[18][19][20] .…”
Section: Resultssupporting
confidence: 72%
“…Furthermore, a total of 13 articles were excluded for the following reasons: 5 for repeat with subsequent studies [22][23][24][25][26] , 3 for inconsistent follow-up visit time [27][28][29] , 3 for the inaccurate and insufficient data [30][31][32] , 1 where grafted material did not fulfil the inclusion criteria 33 , and 1 was excluded for the inaccurate demographic data 34 . Finally, 18 studies were included in this systematic review and meta-analysis, among which were 13 non-grafted TSFE [35][36][37][38][39][40][41][42][43][44][45][46][47] , 5 TSFE grafted with various platelet concentrations (PRP, PRF, CGF or PRGF) 7,[18][19][20][21] . Tables 1 and 2 shows the literature quality assessments of the 3 controlled studies and 15 non-randomized studies.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, maxillary sinus elevation was within 4 mm. Under these conditions, previous studies have shown that bone can be formed effectively without bone graft materials . The osteogenesis in alveolar fossa is primarily caused by blood clots around the implant.…”
Section: Discussionmentioning
confidence: 99%
“…Under these conditions, previous studies have shown that bone can be formed effectively without bone graft materials. 30 The osteogenesis in alveolar fossa is primarily caused by blood clots around the implant. No artificial bone grafts was implanted into the alveolar socket in the test group, and the gap disappeared 6 months after operation.…”
Section: Discussionmentioning
confidence: 99%
“…These reference lines are the same as those used in the studies by Si et al (Si et al, 2013;Si et al, 2016). First, the implant axis {a} is drawn in green.…”
Section: Radiographic Reference Linesmentioning
confidence: 99%